A one-layer recurrent neural network for non-smooth convex optimization subject to linear inequality constraints - Liu, Xiaolan; Zhou, Mi (Chaos, solitons and fractals, 2016)
In this paper, a one-layer recurrent network is proposed for solving a non-smooth convex optimization subject to linear inequality constraints. Compared with the existing neural networks for optimization, the proposed neural network is capable of solving more general convex optimization with linear inequality constraints. The convergence of the state variables of the proposed neural network to achieve solution optimality is guaranteed as long as the designed parameters in the model are larger than the derived lower bounds.